Evaluation of an automatic platelet counting system utilizing whole blood - Rowan, R. M. (1972)
Technicon's newly developed platelet AutoCounter utilizes an electro-optical system which detects and counts particles by sensing the scattering of light which occurs when blood cells flow through the illuminated sensing chamber of a micro-optical system. The system utilizes whole blood collected into EDTA. Blood samples, which can be handled at the rate of 40 per hour, are diluted with 2M urea which in addition causes lysis of the erythrocytes. The haemolysate thus obtained is delivered to the particle counter after a two-minute reaction time, the cell count finally being displayed on a continuous chart recorder. An evaluation of this machine has been carried out in the Department of Haematology, the Royal Infirmary, Edinburgh, on hospital specimens from patients suffering from a wide variety of diseases. The results of this evaluation are presented. Reproducibility studies indicate a coefficient of variation of 4% at any platelet level. The percentage drift per sample ranges from +0·4 to −0·4% of the total count. Carry-over and departures from linearity are statistically significant; however, the magnitude of these deviations is not sufficient to cause concern in routine use. Acceptable agreement is noted between machine counts and the counts obtained by technicians using phase-contrast microscopy with the exception of two anomalous individuals. Discrepant counts were noted in patients with elevation of the erythrocyte sedimentation rate and also in patients with disturbance of immunoglobulins. A modification to the sampling probe which eliminates the former problem is described. The AutoCounter described in this paper provides a fast, reliable, and accurate service laboratory platelet counting system.